Crossrail project : infrastructure design and construction - Black, Mike (Engineering geologist); Dodge, Christian; Lawrence, Ursula (ICE Publishing, 2015)
The construction of the Crossrail project began at North Dock in Canary Wharf in May 2009. Five years on, it is the biggest railway construction project in Europe and is one of the largest single infrastructure investments undertaken in the UK. It consists of 21 km of new twin-bore tunnels under central London and 10 new world-class stations constructed under the largest city in the European Union. This work contains a collection of 36 papers submitted to Crossrail's Technical Papers Competition between 2012 and 2013.